Práctica lectora y ejercicio ciudadano en Galápagos - Agea, Omar Adrian (2017)
The capital of the Ecuadorian archipelago is a populated area in which the central government hasn’t achieved to promote integral intellectual and cultural development. The lack of politics in the matters has created problems in the appropriation of constructive activities such as reading. The limited politic interest in the stimulation of projects, and the creation of specialised areas that provide intellectual attention that promote participatory endeavours, makes the development of the public sphere difficult. The low activity related to social, cultural and communicative practices of the residents of Puerto Baquerizo Moreno community, generates deficiencies in the citizen exercise. Understanding this exercise as the positive attitude towards improving the actual reality of the society by the critic thought related and the skill of participation with social conscience and cognitive freedom. This problem makes you wonder: How a community can make use of the correct exercise of their citizenship, if they don’t posses the adequate reading practice that develops and enhances the intellectual skills of the citizens? This work allows the development of awareness of a social critic thinking that shows the intellectual reality of the capital of the archipelago. Exposes then the important the reading turns out to be for the development of the societies, allowing reaching plain cognitive skills, which reduces the possibilities of social vulnerability for the development of the citizen drive. Establishing a document where academic arguments will allow a theory based idea to improving the citizen participation in the Galapagos and its life quality.